Symmetries and reductions of Dirac-Jacobi structures (2021)
In this manuscript we study reductions of Dirac-Jacobi structures on a smooth manifold under the presence of symmetries given by the action of a connected Lie group. The main tools we used are the called "homogenization trick" and the well known reduction of Dirac structures. We show two particular cases, namely, reduction by moment map and the case when the base manifold is endowed with a contact 1-form.